688 How much do disuse syndrome patients improve with convalescent rehabilitation? Assessment of improvement (Balneo and PRM Research Journal, 2024)
The purpose of this study is to analyse the therapeutic effects of patients with disuse syndrome who underwent rehabilitation. The subjects were 168 patients (87 male and 81 female). We investigated the relationship between the degree of FIM gain and etiology, age, gender, history of cerebrovascular disease, dementia, body weight, body mass index(BMI), hemoglobin, protein, albumin, prognostic nutritional index, malnutrition and dysphagia. The main etiologies that resulted in disuse syndrome were COVID-19, respiratory disease, gastrointestinal disease, urinary disease, cardio-vascular disease1, and others . The average FIM-total gain by age decreased as age increased. FIM-total gain was 8.0 for the patients in their 90s. FIM-total gain was 13.8 for those with no past incident of cerebrovascular diseases, 7.6 for one past incident, and 4.0 for two or more past incidents. FIM-total gain of the patients of severe dysphagia was significantly lower than that of the patients of normophagia / mild or moderate dysphagia. There was mild correlation between FIM-total gain and gain of body weight (r=0.21) and between FIM-total gain and gain of BMI (r=0.21).  Patients with disuse syndrome over 90s or with two or more incidents of cerebrovascular diseases should be treated, not in rehabilitation but in nursing care.